Velocity characteristics of coaxial nozzle flows with a central lobed mixer - Xu, Xiang Guo. (2009)
Measurements have been conducted downstream of a two-dimensional lobed forced mixer in a wind tunnel and downstream of coaxial nozzles with and without a central three-dimensional lobed mixer in a water tunnel. In the wind tunnel experiment, a two-dimensional lobed mixer with six full lobes was tested at different velocity ratios. At each velocity ratio, four different thicknesses of initial boundary layer had been used. The velocity measurements were obtained at a Reynolds number of 2.27x10 (based on the nominal wavelength of the lobe at 33 mm and the mean speed of the two streams at 10 m/s) using a three-hole pressure probe. Results highlighted that large velocity ratios and thick initial boundary layers would normally lead to a faster decay rate for the streamwise vorticity downstream of the lobed mixer trailing edge.